PENGARUH MOTIVASI, PERSEPSI, SIKAP KONSUMEN DAN PEMBELAJARAN TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE âBLACKBERRYâ (Studi Pada Masyarakat di Kota Semarang) - Asa Bangkit Probo Pratista, 0625020025; Maskur, Ali (Students Journal of Economic and Management, 2014)
The development of technology, especially mobile technology today, that is worthy of attention, this is because almost all mobile phone to know the age limit , and even almost all walks of life use cell phones in their everyday lives , in connection with it, the BlackBerry nowadays become trend in society Indonesia, Semarang in particular.This study examined how the influence of consumer motivation, consumer perception, consumer attitudes and consumer study on purchasing decisions smartphones